Fasting-mimicking diet synergizes with ferroptosis against quiescent, chemotherapy-resistant cells - Xiaoxia Liu; Shaoyong Peng; Guannan Tang; Gaopo Xu; Yumo Xie; Dingcheng Shen; Mingxuan Zhu; Yaoyi Huang; Xiaolin Wang; Huichuan Yu; Meijin Huang; Yanxin Luo (2023)
More than ten randomized clinical trials are being tested to evaluate the efficacy, effectiveness and safety of a fasting-mimicking diet (FMD) combined with different antitumor agents.UMI-mRNA sequencing, Cell-cycle analysis, Label retention, metabolomics, Multilabeling et al. were used to explore mechanisms. A tandem mRFP-GFP-tagged LC3B, Annexin-V-FITC Apoptosis, TUNEL, H&E, Ki-67 and animal model was used to search for synergistic drugs.Here we showed that fasting or FMD retards tumor growth more effectively but does not increase 5-fluorouracil/oxaliplatin (5-FU/OXA) sensitivity to apoptosis in vitro and in vivo. Mechanistically, we demonstrated that CRC cells would switch from an active proliferative to a slow-cycling state during fasting. Furthermore, metabolomics shows cell proliferation was decreased to survive nutrient stress in vivo, as evidenced by a low level of adenosine and deoxyadenosine monophosphate. CRC cells would decrease proliferation to achieve increased survival and relapse after chemotherapy. In addition, these fasting-induced quiescent cells were more prone to develop drug-tolerant persister (DTP) tumor cells postulated to be responsible for cancer relapse and metastasis. Then, UMI-mRNA sequencing uncovered the ferroptosis pathway as the pathway most influenced by fasting. Combining fasting with ferroptosis inducer treatment leads to tumor inhibition and eradication of quiescent cells by boosting autophagy.Our results suggest that ferroptosis could improve the antitumor activity of FMD + chemotherapy and highlight a potential therapeutic opportunity to avoid DTP cells-driven tumor relapse and therapy failure.A full list of funding bodies can be found in the Acknowledgements section.